Die doel en wese van opvoedende onderwys en die implikasies daarvan vir omgewingsopvoeding - Henning Viljoen (Environmental Association of Southern Africa, 1988)
The broad aim of education is to supply the learner with relevant knowledge, skills and values to enable him/her to positively contribute to life and in doing so making his/her life worthwhile. Education is a holistic process considering a wide variety of human aspects. Therefore by omitting some of these aspects e.g. sound conservation-value teaching, the learner is not fully prepared for life. Environmental education is an important tool in reaching the goals of 'universal education' 'education of the whole person'- 'education for life'.